Federici, F. M., Declercq, C. (Eds.). (2021). Intercultural Crisis Communication: Translation, Interpreting and Languages in Local Crises. Bloomsbury Academic. (pp. 280) http://dx.doi.org/10.5040/9781350097087 - Zhang, Shaoqiang; Jia, Huihuang (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
Book review